Geological Characteristics of the Mesozoic Unconformities in Eastern Heilongjiang, NE China: Implications for the Mesozoic Continental Margin Evolution of Northeast Asia - Zhao, Xueqin; Lv, Congcong; Jiang, Yaoxi; Zhu, Heyan; Wang, Fudong; Chai, Peiran (Frontiers in Earth Science, 2022)
The origin of significant petroleum and coal-bearing sedimentary basins in Northeast Asian is inferred to be dominated by rifting and thermal subsidence, followed by basin inversion. However, the inference has not been fully proved or explained in tectonic and geodynamic model. To solve this problem, we analysed tectonic characteristics and geodynamic background of the Mesozoic continental margin basins evolution in Northeast Asian by a synthesis information of regional Mesozoic unconformities from seismic reflection profiles and field outcrops in Eastern Heilongjiang Province (EHLJ), northeast China. The results show that five regional Mesozoic unconformities in the EHIJ can be recognised. The five unconformities reflect the tectonic evolution of NE China was controlled by two-sided active continental margin tectonics of the Mongol–Okhotsk Belt suturing in the north, and the Pacific Plate subduction in the east. While this control also showed the shift towards the increasing dominance of the Pacific Plate subduction.